Modal Analysis of the Wind Turbine Planned to be Built in Mamurdağı Ground Conditions Using Finite Element Method - Aydın, Hakan (International Conference on Applied Engineering and Natural Sciences, 2023)
In the present study, steel structural wind turbine tower with design configurations is analysed using ABACUS CAE 2022 FEM modelling. Tower of 73m heights is considered and investigated with dynamic parameters, mechanical design options. Structural and dynamic analyzes of the wind turbine, which is thought to be built in the Mamurdağ location of Samsun İlkadım District, has been tried to be analyzed using the Finite Element Method.The main purpose of this study is to numerically examine the dynamic behavior of the wind turbine under the existing ground conditions of Mamurdağı for the Wind Turbine. The turbine preferred as a model in this study is the 73m high 800Kw wind turbine belonging to Enocon Company. Modeling was made in the light of the technical data of the relevant company. While the numerical model was being created, the blades of the wind turbine and the nacelle-rotor system were not modeled, but the actual weight, corresponding to approximately 81 tons was applied as a load to the system. In the last part of the article, the dynamic properties of this 73m high tower are examined to obtain the natural frequencies and mode shapes. As a result of the analysis, 5 different mode shapes, frequency and period values of the wind turbine planned to be built were obtained. According to the modal analysis results of the wind turbine, the result of the dominant frequency was obtained as 0.72327 (cycles/time). First Mode is in the y-x plane so this is the lateral movement in this direction.